The Perceived Value For International Halal Makeup Product In Thailand - Ismaja, Delvicka; Kijkasiwat, Ploypailin (Universitas Muhammadiyah Magelang, 2022)
The current level of awareness of halal cosmetics is still low. The main reason behind this phenomenon lies in the scarcity of halal cosmetics on the market. Due to a lack of understanding of halal and haram/halal, consumers in turn lack awareness of halal products. Despite the industry's potential, consumers are not adequately exposed to halal brands, and as a result, halal cosmetic items have a poor level of reactivity. Gaining a better understanding of how consumers view halal cosmetic brands is essential. Most of the available literature on halal matters has primarily been undertaken in food science, with studies on the cosmetic business receiving little attention. Even though a few studies on halal cosmetics exist, most of them rely on anecdotes and case studies, with the majority considering the role of theory of reasoned action (TRA) in purchasing behavior. Thus, this study aimed to examine Thai people's knowledge about halal makeup and their awareness, and how product quality and perceived value can influence customer satisfaction. Data were collected using online questionnaires distributed to the consumers selected by the clustered sampling method. The questionnaires were distributed in some areas across the provinces in Thailand. The population was makeup users, e.g., Thai people or Muslin or non-Muslim people residing in Thailand. With Thailand’s population of 70,030,726, a sample of 400 consumers in various regions in Thailand, e.g. men and women with an age range of 16-50 years, was invited to fill out a research questionnaire based on the aims and interests of the research.